(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background and aims: Type 2 diabetes, the modern epidemic has recently known to be associated with cognition dysfunction and dementia, the detection of which appears to be the tip of the iceberg as majority of the cases still remains undiagnosed. With the increase in the prevalence of type 2 diabetes mellitus and neurodegenerative diseases,it is worthwhile to warrant a screening for cognition function in type 2 diabetes mellitus. The study was done to evaluate the cognition status using MoCA score in type 2 diabetes mellitus and age and sex matched control and to correlate the MoCA score with Glycemic status and BMI. Material and method: The study involved 41 cases of type 2 diabetes mellitus and 41 controls. Cognition status was assessed using MoCA score. A score of > 26 was considered as normal cognition. Fasting Plasma Glucose (FPG) was measured by Hexokinase method. HbA1c was assessed by Turbidimetric inhibition method BMI was Calculated as weight (kg)/ height2 (m). Data was expressed as mean ± SD. Comparison of the data was done by using unpaired t test. Correlation of the parameters was done by using Pearson’s correlation test. p < 0.05 was considered statistically significant.Conclusions: Cognitive decline observed emphasis the need for a routine screening of cognition status in type 2 diabetes mellitus and to identify sensitive and specific biomarkers for early detection of cognitive decline in type 2 diabetic patients.